Climate dialog, climate action: Can democracy do the job? - Fred Young Philips; LaVonne Reimer; Rebecca Turner (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The latest IPCC report forcefully states that immediate, decisive, and large-scale actions are needed to avert climate catastrophe. This essay presumes that democratic governments are best and most desirably positioned to take these actions. Yet in the countries most pivotal to global climate change, significant voting blocs are uninterested in environmental issues. The essay urges adding bottom-up dialog between environmental and anti-environmental voters, to current and future top-down technocratic "solutions". To make this combination result in a unified pro-environment electorate, we must understand: religious objections to environmentalism; the capital-vs.-knowledge strife that slows polluting corporations' green transitions; and the psychological mechanisms that can make inter-group dialog fruitful.
Keywords: 650; climate; democracy; religion; evangelism; environment